2020
DOI: 10.1111/ppc.12562
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of social support in the effect of perceived organizational support and psychological empowerment on career satisfaction in nurses

Abstract: Purpose: This research was to investigate the mediating role of social support in the effect of perceived organizational support and psychological empowerment on career satisfaction in nurses. Design and Methods: This predictive study was carried out with 442 nurses in 2019. The research variables were analyzed factor analysis, correlation analysis, regression analysis, Sobel tests. Findings: The study, it was determined that social support had a partial mediating role in the effect of perceived organizational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
0
10
0
4
Order By: Relevance
“…The 30 articles that review (Table 2) in 19 articles expressed social support have a positive relationship results and have a significant influence on the work satisfaction of nurses [9], [37], [11], [13], [10], [3], [12], [15], [21], [22], [28], [14], [32], [34], four articles expressed social support and work satisfaction that have an effect directly affecting psychological distress [16], [17], [34], [20], one article [35] expressed social and job satisfaction significantly affects the intention of nurses to stay and not leave his job, two articles show that social support has a partial mediating role in the effect of psychological empowerment on career satisfaction of nurses in the hospital [24], [33], two articles show that nurses are one of the most important occupations under the influence of the social support approach because of their direct communication with patients and clients [27] and [31], one article shows that social support on behavior at work suggests practical implications intervention to increase the stability of nurses who work in tertiary hospitals in China [29], and one articles shows social support at the individual level such as nurses and organizations to improve the quality of nursing in the working life of the hospital in providing health services [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 30 articles that review (Table 2) in 19 articles expressed social support have a positive relationship results and have a significant influence on the work satisfaction of nurses [9], [37], [11], [13], [10], [3], [12], [15], [21], [22], [28], [14], [32], [34], four articles expressed social support and work satisfaction that have an effect directly affecting psychological distress [16], [17], [34], [20], one article [35] expressed social and job satisfaction significantly affects the intention of nurses to stay and not leave his job, two articles show that social support has a partial mediating role in the effect of psychological empowerment on career satisfaction of nurses in the hospital [24], [33], two articles show that nurses are one of the most important occupations under the influence of the social support approach because of their direct communication with patients and clients [27] and [31], one article shows that social support on behavior at work suggests practical implications intervention to increase the stability of nurses who work in tertiary hospitals in China [29], and one articles shows social support at the individual level such as nurses and organizations to improve the quality of nursing in the working life of the hospital in providing health services [30].…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 30 articles, 28 used the questionnaire survey [3], [38], [10], [11], [39], [13], [14], [15], [16], [17] [18], [19], [20], [21], [22], [24], [25], [26], [28], [29], [30], [31], [32], [33], [34], [35], [36], [38]. One article using articles review [27] and one article using the post-test control variable design [12].…”
Section: Intervention Methodsmentioning
confidence: 99%
“…Meanwhile, other studies also found that individuals with higher levels of psychological empowerment tend to exhibit higher career satisfaction [ 18 , 22 , 23 , 24 ]. For example, Blais et al analyzed the dimension of work fatigue among military and civilian employees.…”
Section: Introductionmentioning
confidence: 97%
“…Psychological empowerment refers to the synthesis of psychological states or cognition experienced by an individual [ 12 , 13 , 14 , 15 ]. Previous research found that both professional identity [ 12 , 16 , 17 ] and career satisfaction [ 18 , 19 , 20 ] are positively correlated with psychological empowerment. According to Cognitive Evaluation Model Theory (CEMT), individuals evaluate themselves and their career condition in conjunction with their own and others’ perspectives, and individuals with positive psychological empowerment would gain a stronger sense of meaning in their work [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perceived organizational support has also been examined in the context of nursing. Researchers found that nurses who perceived organizational support experienced higher career and job satisfaction ( Polat and Terzi, 2020 ; Türe and Akkoç, 2020 ), were less likely to report chronic fatigue syndrome ( Li M. et al, 2020 ), and were less likely to intend to leave nursing ( Li X. et al, 2020 ). Further, a study of nurses during the SARS pandemic found that perceptions of organizational support predicted lower levels of avoidance behaviors, emotional exhaustion, and nurse anger ( Marjanovic et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%